Multiplexing Recent Advances and Novel Applications - Mohammady, Somayeh (IntechOpen, 2022)
The idea of sharing a medium between signals originated sometime in the late 18th century and first appeared in wired telephone systems in the United States in the early 19th century. Multiplexing (MUX), a method by which multiple analog or digital signals are combined into one signal over a shared medium, increases the capacity of the communication channel by dividing it into several logical channels, one for each message signal or data stream to be transferred. On the receiver side, the reverse process known as de-multiplexing (DEMUX) helps to extract the original channel. This book examines recent advances and novel applications in MUX and DEMUX. It discusses how MUX is applied in free-space optics (FSO) applications and how 5G and 6G signals benefit from MUX, among other topics.